PENGARUH IKLIM ORGANISASI, KEPEMIMPINAN, DAN KOMPENSASI TERHADAP LOYALITAS PEGAWAI - Astuti, Prihartini Budi; Prayoga, Singgih Septiyan (Jurnal Fokus Manajemen Bisnis, 2021)
This study was conducted to determine the effect of organization climate, leadership, and salary to employee loyalty in Disdukcapil Kebumen Regency Organization. This study was conducted in quantitative method by using all members of population (42 employees) as the respondents. The collected data then being analyzed by using SPSS to test the multiple linier regression, T test, F test, and coefficient of determination. The result showed that the regression model of the study has fulfilled all of the classical assumption tests. The t test result showed that there are positive and significant partial correlations between organization climate, leadership, and salary to employee loyalty in Disdukcapil Kebumen Regency Organization.Â